KAITAN ANTARA PERSEPSI PESERTA TERHADAP PASAR LELANG DENGAN SIKAP PESERTA PASAR LELANG AGROFORWARD DI PROVINSI JAMBI - Nida Kemala; Siti Abir Wulandari (Universitas Batanghari Jambi, 2014)
The research was applied in the Agroforward Auction Market that conducted at Jambi Province. It was held in order to find the description of some variables i.e. the perception of the market participants and their attitude toward to this market system.The snow ball sampling technic was applied to find 25 samples and it is completed by applying the Chi-Square Test as analysis instrument in this research.The result of the research showed that this market participants has a good perception (76%) and positif attitude toward to Agroforward Auction Market (76%). Beside there were significantly relationship between their perception on this market system and their attitude toward to this agroforward auction market system.Key word : agroforward, auction.Market.